2021
DOI: 10.3390/pharmaceutics13060773
|View full text |Cite
|
Sign up to set email alerts
|

Challenge in the Discovery of New Drugs: Antimicrobial Peptides against WHO-List of Critical and High-Priority Bacteria

Abstract: Bacterial resistance has intensified in recent years due to the uncontrolled use of conventional drugs, and new bacterial strains with multiple resistance have been reported. This problem may be solved by using antimicrobial peptides (AMPs), which fulfill their bactericidal activity without developing much bacterial resistance. The rapid interaction between AMPs and the bacterial cell membrane means that the bacteria cannot easily develop resistance mechanisms. In addition, various drugs for clinical use have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 117 publications
(91 reference statements)
0
25
0
Order By: Relevance
“…Both AMPs and AgNPs have demonstrated their potential in combating resistant microbes (Lara et al, 2010;Rai et al, 2012;Roque-Borda et al, 2021), and both have also been found to act synergistically with conventional antibiotics (Cassone and Otvos, 2010;Wan et al, 2016;Krychowiak et al, 2018;Ruden et al, 2019;Zharkova et al, 2019;Duong et al, 2021). Moreover, it has previously been reported by us (Zharkova et al, 2019) as well as by others (Ruden et al, 2009;Salouti et al, 2016), that AMPs and AgNPs can enhance each other's antimicrobial activity, when used in combination.…”
Section: Introductionmentioning
confidence: 91%
“…Both AMPs and AgNPs have demonstrated their potential in combating resistant microbes (Lara et al, 2010;Rai et al, 2012;Roque-Borda et al, 2021), and both have also been found to act synergistically with conventional antibiotics (Cassone and Otvos, 2010;Wan et al, 2016;Krychowiak et al, 2018;Ruden et al, 2019;Zharkova et al, 2019;Duong et al, 2021). Moreover, it has previously been reported by us (Zharkova et al, 2019) as well as by others (Ruden et al, 2009;Salouti et al, 2016), that AMPs and AgNPs can enhance each other's antimicrobial activity, when used in combination.…”
Section: Introductionmentioning
confidence: 91%
“…Diseases related to these bacteria develop slowly, allowing for greater adaptation and production of biofilm and subsequently leading to severe local inflammation [ 6 ]. The increasing cases of hospital infections, mainly highly lethal urinary tract and bloodstream infections caused by biofilm-forming bacteria in medical equipment, have concerned the World Health Organization (WHO) and led it to publish a list of priority bacteria for study and drug discovery [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impaired quality of life, combined with the development of systemic bacterial infections, the increase in recurrence rates, chronicity, and the development of future opportunistic infections with resistant organisms are the consequences of bacterial infections caused by antibiotic-resistant organisms, such as MDR, XDR, and pan-drug-resistant (PDR) strains [ 13 ]. Therefore, AMR is a serious problem that affects several areas beyond modern medicine and the pharmaceutical industry, intensified by the resulting serious socio-economic and ecological impacts [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…All multicellular organisms naturally express these molecules as innate immune response elements that synchronise multiple tasks in and outside the cells [12,13]. Examples of the putative functions of HDPs include (1) eliminating bacterial growth through the direct antimicrobial activity without generating resistance [14][15][16], (2) inhibiting and eradicating biofilms by promoting dispersal and abolition through inhibition of biofilm-specific signalling pathways [17][18][19][20][21], and…”
Section: Introductionmentioning
confidence: 99%
“…Pharmaceutics 2021, 13, x FOR PEER REVIEW 2 of 24 include (1) eliminating bacterial growth through the direct antimicrobial activity without generating resistance [14][15][16], (2) inhibiting and eradicating biofilms by promoting dispersal and abolition through inhibition of biofilm-specific signalling pathways [17][18][19][20][21], and…”
Section: Introductionmentioning
confidence: 99%